An Evaluation of Teaching Stratergies Prescribed by TIM to Teach Science at Grade Eight in Sri Lanka - Karunasena, N.V. (University of Colombo, 2010)
After 1972 educational reforms were implemented science became a compulsory subject in Sri Lanka at junior secondary level. The subject is identified as very important due to its higher educational value. The most important value is the potential of science to develop the rational powers of students (Lawson, 1995). Thinking abilities related to science processes are essential in the intellectual development of the students. The knowledge, skills and attitudes which can be developed by science are very necessary for all individuals, society and the human kind. During the decades 1960 and 1970, science education in the world was developed by identifying Process Based Science Teaching and Beyond Process Science Teaching. This effort rejected the Product Based Science Teaching. Mere teaching of scientific knowledge is useless when the Process of Science and Influence of Science are neglected. It is very important to evaluate the science curriculum in Sri Lanka. This effort is to evaluate the recommended teaching stratergies of science at grade eight in Sri Lanka in the Teacher Instructional Manual (TIM). The objectives of the study are to find out the strategies prescribed by the TIM and evaluate them, whether they are suitable for the science teaching with reference to the nature of science and the educational values of science. Science instructional manual was perused with a checklist prepared which includes the most recommended teaching stratergies of science and visible strategies recommended in TIM Grade Eight science curriculum consists of eight units and 33 sub units/lessons.30 lessons are recommended to be taught using written texts. Here dialogues and poems are used as methods of teaching science. Observations or testing strategies are used only in five instances. Therefore it is concluded that the stratergies recommended are not appropriate to teach science.